Utilization of Geogle Earth Engine for Flood Hazard Analysis in DKI Jakarta Province - Sugandhi, Nandhi; Rakuasa, Heinrich (PT. Riset Press International, 2023)
This research describes the use of Google Earth Engine as a key tool in analyzing flood vulnerability in DKI Jakarta Province. By combining high-quality satellite data, detailed city surface mapping, and advanced geospatial analysis capabilities, this technology has opened the door to a deeper understanding of the factors that influence flood risk in this densely populated region. This research uses the variables distance from river, elevation, TPI (Topographic Position Index) and NDVI (Normalized Difference Vegetation Index). Processing and analysis in this research was carried out in Google Earth Engine. The results of this study indicate that the area at the low flood vulnerability level has an area of 14,735.61 ha or 22.53%, the area at the medium vulnerability level is 32,512.94 ha or 49.71% and the area at the high flood vulnerability level is 18,153.42 ha or 27.76%. The results of this research are expected to help the DKI Jakarta Provincial Government in flood mitigation.